(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article explores the semantic field of “clothes” in the English and Uzbek languages. The analysis is based on a comparative study of lexical items related to clothing in the two languages, including words for garments, fabrics, colors, and accessories. The study reveals significant similarities and differences between the two languages in terms of the semantic associations and connotations of clothing-related vocabulary. While both English and Uzbek have a rich lexicon of clothing-related terms, there are notable variations in the way these terms are used and perceived by speakers of each language. These variations reflect not only linguistic differences but also cultural and historical factors that shape the way people think about and interact with clothing. Overall, this study contributes to our understanding of how language reflects and shapes cultural practices related to dress and fashion.